Implementation of Pure Pursuit Algorithm for Nonholonomic Mobile Robot using Robot Operating System - Aydogmus, Omur; Boztas, Gullu (My University, 2021)
In this study, a differential wheeled mobile robot was controlled in real time using pure pursuit algorithm (PPA). The robot was obtained in a simulation environment by using Gazebo simulator which offer the ability to accurately and efficiently simulate various robots in complex indoor/outdoor environments. This simulator was operated with robot operating system (ROS) that allows the use of Python, C++, MATLAB or various programming languages. In this paper, MATLAB/Simulink environment was used to control the robot with communication interface between MATLAB and ROS. Thus, it is possible to study more comprehensively by using multiple the features of MATLAB. The robot was traveled around a 4m x 4m area with random waypoints. The position of the robot was measured based on odometer sensor in order to determine the robot’s location. The performance of the control algorithm was analyzed using various information of the robot such as robot’s velocity, motors’ speed, the position of the robot, etc.
Keywords: Mobile Robot; Robot Operating System; Pure Pursuit Algorithm